The impact of E-education and innovation on unemployment reduction among graduates: A way forward for higher educational institutes - Mian, Lu; Hussin, Ridzuan; Slaninová, Mgr. Gabriela; Shahzadi, Yusra (Frontiers in Psychology, 2022)
Recently, the use of digital skills as a tool to alleviate unemployment concerns of university graduates has gained considerable attention among governments in developing economies. The present study examines the impact of the E-education program (a digital initiative to train university graduates to get self-employed) on the unemployment reduction of young graduates of higher educational institutes (HEIs). We also explore the mediating influence of innovation in the association between E-education and unemployment reduction. The target population of the study was students who have successfully completed the E-education program. The convenient sampling technique was used for data collection from 416 respondents through a structured questionnaire. Collected data were analyzed using different statistical techniques, such as descriptive statistics (reliability analysis, normality analysis, and correlation) and structural equation modeling for measurement of the structural model. The study findings assert that the E-education program has significant effects on the unemployment reduction of graduates. Furthermore, innovation also significantly mediates the association between E-education and reduce unemployment among students. It implies that the HEIs should also roll out E-education programs, which would eventually help reduce unemployment and promote the growth of the E-education industry in the country. Finally, policy prescriptions are discussed on the role of an E-education-driven innovation to curtail unemployment in developing countries.